Development of a PROM to measure patient-centredness in chronic care consultations in primary care - Anne Holm; Anna Bernhardt Lyhnebeck; Sussi Friis Buhl; Kristine Bissenbakker; Jette Kolding Kristensen; Anne Møller; Anders Prior; Zaza Kamper-Jørgensen; Sidsel Böcher; Mads Aage Toft Kristensen; Asger Waagepetersen; Anders Hye Dalsgaard; et al. (Health and Quality of Life Outcomes)
Abstract Introduction Validated patient-reported outcome measures (PROMs) are crucial for assessing patients’ experiences in the healthcare system. Both clinically and theoretically, patient-centered consultations are essential in patient-care, and are often suggested as the optimal strategy in caring for patients with multimorbidity. Aim To either identify or develop and validate a patient-reported outcome measure (PROM) to assess patient-centredness in consultations for patients with multimorbidity in general practice. Methods We attempted to identify an existing PROM through a systematic literature review. If a suitable PROM was not identified, we planned to (1) construct a draft PROM based on items from existing PROMs, (2) conduct group and individual interviews among members of the target population to ensure comprehensibility, comprehensiveness and relevance, and (3) perform a psychometric validation in a broad sample of patients from primary care. Results We did not identify an eligible PROM in the literature review. The item extraction and face validity meetings resulted in a new PROM consisting of 47 items divided into five domains: biopsychosocial perspective; `patient-as-person’; sharing power and responsibility; therapeutic alliance; and coordinated care. The interviews resulted in a number of changes to the layout and phrasing as well as the deletion of items. The PROM used in the psychometric validation consisted of 28 items. Psychometric validation showed high internal consistency, overall high reliability, and moderate fit indices in the confirmatory factor analysis for all five domains. Few items demonstrated differential item functioning concerning variables such as age, sex, and education. Conclusions This study successfully developed and validated a PROM to measure patient-centredness in consultations for patients with multimorbidity. The five domains demonstrated high reliability and validity, making it a valuable tool for measuring patient-centredness of consultations in general practice. Trial registration Trial registration number (data for psychometric validation): https://clinicaltrials.gov : NCT05676541 Registration Date: 2022-12-16.